Analysis of the Role of Business Processes in Enhancing Strategy, Policy, and Performance in the Private and Public Sectors: A Literature Review - Insani, Nurlita Sukma; Sayuti, Muhamad; Suhara, Ade; Hakim, Afif (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
This study aims to conduct a systematic literature review of recent research addressing the implementation and development of business processes within the public and private sectors. 150 articles from various databases were collected and screened using inclusion and exclusion criteria, resulting in 50 relevant articles selected for further analysis. The analysis involved classifying the articles based on functional business areas and contributions to organizations, namely strategy, performance, and policy, as well as identifying the challenges and success factors in business process implementation. The findings reveal that strategic contributions are the primary focus of the literature, particularly in the areas of operations management, digital transformation, and technological innovation. The main challenges identified include the integration of advanced technologies, organizational readiness, and supply chain coordination. On the other hand, the success factors found include digital technology adoption, strengthening of organizational capabilities, and transformational leadership. This study provides both theoretical and practical contributions to understanding the dynamics of modern business processes and serves as a reference for the development of more adaptive and sustainable organizational strategies and policies in the digital era.